Parking Adequacy around Wet Market, Iligan City - Cantila, Kenny (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2022)
The study determines the parking adequacy around Gaisano Store using the parking inventory and the usage study. Parking adequacy is the difference between the effective parking supply and the average parking demand. It is considered “surplus” when the value is positive and “deficit” when the value is negative. From the entire survey duration, results show that on an hourly basis, Quezon Avenue has the highest deficiency in the parking supply at 72%, followed by Cabili Avenue at 36%, Nanaman Street at 29%, Baslayan Street at 19%, and Mercado Street at 13%. Only the Aguinaldo Street has a surplus in the parking supply at 18%. In general, the study shows that the parking supply around the study area is insufficient. Hence, there is a need to properly manage the existing parking facility.